Influence of structural setting, depositional environment and differential diagenesis on reservoir quality of the Xixiangchi formation in the central and southern Sichuan Basin, China - Chen, Shizhen; Wen, Huaguo; Li, Xiang; Huo, Fei; Mo, Bowen; Liang, Jintong; Duan, Lian (Frontiers in Earth Science, 2025)
The Middle-Upper Cambrian Xixiangchi Formation (504 - 488 Ma) dolomite in the central-southern Sichuan Basin constitutes significant hydrocarbon reservoirs, though their complex genetic mechanisms remain inadequately constrained. This study investigates dolomite types within the Xixiangchi Formation through petrography, physical property analysis, and geochemical analyses (C - O isotopes, rare earth elements) to elucidate reservoir characteristics and diagenetic evolution. Reservoir lithologies comprise four dolomite types: microcrystalline dolomite (≤31 μm, D1), fabric-retentive dolomite (<100 μm, D2), very finely to finely crystalline dolomite (31 ∼ 100 μm, D3), and finely to medium crystalline dolomite (100 ∼ 300 μm, D4). All dolomite types exhibit rare earth element patterns and isotopic signatures (δ13C: −1.39‰ ± 0.67‰ to - 1.23‰ ± 0.71‰; δ18O: −8.62‰ ± 1.18‰ to - 8.15‰ ± 0.98‰) comparable to coeval micritic limestones, indicating formation from evaporatively-concentrated seawater or marine-derived fluids. D1 displays laminated textures with relatively elevated δ18O values and minimal Fe-Mn concentrations, consistent with near-surface precipitation. D2 exhibits coarser grain size, reduced Ce anomaly intensity (0.92 ± 0.06) compared to micritic dolomite, and lower δ18O values, indicating its formation during shallow-to-moderate burial diagenesis, possibly associated with downward percolation-reflux of Mg2+-rich evaporative brines. D3 and D4 show mosaic contact and granular phantom textures, along with lower Ce anomaly intensities (0.93 ± 0.05, 0.91 ± 0.6) and decreased total rare earth element contents, which imply a deeper diagenetic environment than that of D2. Genetic analysis reveals D1-D2 originated through penecontemporaneous evaporative dolomitization and shallow reflux processes, while D3 - D4 formed via burial dolomitization and dolomite recrystallization. D2 is the dolomite type with the best reservoir performance in the Xixiangchi Formation, mainly developed in high-energy sedimentary facies. Early seepage-reflux dolomitization and atmospheric freshwater dissolution are crucial for reservoir development. Burial dolomitization promotes secondary pore development in D3 and D4, increasing porosity, but recrystallization blurs crystal grains and reduces porosity. Evaporation dolomitization creates dense dolomite, making D1 have the poorest porosity. In conclusion, reservoir quality primarily depends on particle shoal development through paleo-uplift and fault-controlled mechanisms, with diagenetic processes (dolomitization, dissolution, fracturing) crucially enhancing porosity preservation and formation.